From Couple Goals to Romantic Expectations: A Qualitative Content Analysis of TikTok Comments - Novita Natarina; Tiara Septia Utami (Jurnal Multidisiplin Indonesia, 2026)
TikTok has become a significant digital platform where romantic relationship representations are produced, consumed, and negotiated among young users. Relationship-themed content, particularly couple goals, often presents idealized portrayals of romance that may influence users’ perceptions, expectations, and interpretations of real-life relationships. This study aims to examine how ideal romantic relationship standards are constructed through TikTok user comments and to explore how social comparison processes emerge within digital interactions. This research employed a qualitative approach using qualitative content analysis. Data were collected from 20 TikTok videos related to couple goals and healthy relationships uploaded between 2024 and 2026, resulting in the analysis of 200 highly engaged user comments selected through purposive sampling. Data were analyzed through inductive thematic analysis using Cultivation Theory and Social Comparison Theory as analytical frameworks. The findings reveal five major themes: the idealization of romantic relationships as emotional standards, upward social comparison, humor and irony as emotional coping mechanisms, critical negotiation of romanticized relationships, and the normalization of healthy relationships as aspirations among younger generations. The results indicate that TikTok functions not only as an entertainment medium but also as an affective digital space where romantic expectations are collectively constructed, reinforced, and challenged. This study concludes that algorithm-driven exposure and user participation contribute to shaping contemporary romantic norms, while also encouraging critical reflection on unrealistic relationship expectations in digital culture.